UNVEILING THE TRAVELLERS’ MIND: A META-ANALYSIS OF TRAVEL DESTINATION CHOICE FACTORS - Babu, S. Ramesh; Murugesan, G. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The term tourism mesmerises human being and make them feel comfortable. People will get excited while selecting travel destination and it is a difficult and time consuming process. In general people consider various factors while selecting their destination to visit. Various researches on tourism identified various factors in deciding the travel destination. This review research followed the guidelines of Preferred Reporting Items for Systematic Review (PRISMA) and identified 80 suitable articles from journals from the databases like Proquest, ResearchGate and Google Scholar. Based on the results of these articles the researcher found that the variables like attitude, subjective norms, perceived behavioural control, destination image, motivation, electronic word of mouth and behavioural intention are shaping the behaviour of travellers in deciding their travel destinations. From these variables destination image plays a major role in deciding the travel location. It also shapes the attitude of the travellers and stimulates the intention to visit that place.